Relationship Between Farmers Weaknesses About Knowledge of Formulation and Feed Technology on Feed Conversion in Alabio Ducks (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aims to determine and analyze the relationship between breeders’ knowledge about feedformulations and the conversion value of duck feed. The subjects in this study were Alabio duck breeders inHambuku Raya Village and Putat Atas Village, Hulu Sungai Utara, South Kalimantan Province, Indonesiawith observed objects in the form of Alabio duck feed conversion and breeders’ knowledge of feedformulation knowledge and Alabio duck feed technology. The research method used was non-experimentalexplorative, the researcher did not give treatment to the group of Alabio ducks and conducted a survey bydistributing questionnaires to farmers. Observation of feed conversion is carried out for 3 (three) monthsfrom February-April 2018 in each group. Observation of feed conversion is carried out starting from Alabioducks to produce eggs, which are about 6 months old. Testing of feed conversion, normal data using analysisof variance (Anova), if significant continued with LSD. Survey research is the stage of analyzing usingSWOT analysis to determine the level of weakness and strength in the framework of the development ofAlabio ducks in the Hulu Sungai Utara Regency of South Kalimantan Province. The results of the analysisof feed conversion of the three groups were not significantly different, the group of Putat Atas Ducks forfeed conversion an average of 4.51 ducks Hambuku Raya 1 group an average of feed conversion everymonth 5.30, the ducks of the Hambuku Raya 2 group the average conversion of feed every month 4.75.SWOT analysis value of weakness factor is 1,764, this factor includes one of them is knowledge of farmersabout feed formulation. The results of this study are in line with the results of feed conversion in the firststage of research, the value of feed conversion obtained is still relatively high at 4.51-5.30. The conclusionis the SWOT analysis score of weakness factors one of which is the lack of knowledge of farmers aboutformulation and feed technology affect the high feed conversion.
Keywords: Alabio duck, feed convertion, SWOT analysis